Fighting and doping: Professional mixed martial artists experience and exposure to performance-enhancing substances and supplements - Woolf, J. R.; Yoon, H.; Perkari, K. (Performance Enhancement & Health, 2021)
In the last few decades, mixed martial arts (MMA) has grown to become a mainstream sport, broadcasted worldwide. The increased commercialization, structure, and physical requirements of the sport arguably make the use of performance-enhancing drugs (PED) attractive to MMA fighters. In contrast, cultural aspects within MMA and diverse expressions of masculinity may temper PED use. Yet, the sport has received little empirical inquiry. This exploratory study sought to understand MMA fighters` experience and exposure to PED and sport supplements. Specifically, how fighters learn about, use, and rationalize the use of these substances was explored, along with cultural aspects of the sport that may influence use. Furthermore, given the rapid rise of this sport, generational differences between veterans and early-career fighters were examined. Seventeen semi-structured interviews with professional MMA fighters were conducted and analyzed using a two-cycle coding method. The presentation of results was organized into four categories: learning and conversing, supplement and PED use, rationalization of use, and MMA contextual factors. Multiple misconceptions existed and the use of both supplements and performance-enhancing substances followed similar justifications linked to recovery, performance enhancement, and deficiency correction. Marijuana emerged as a debated performance-enhancing substance. Experimentation was common and knowledge acquisition strategies differed based on career stage and standing within the fighting and doping community. Fighters acknowledged the pressure to dope. However, cultural aspects of the sport and a purity perspective provide deterrents to both supplement and PED use. The implications of these findings, along with recommendations for future research are discussed.